Analisis Faktor-Faktor yang Berhubungan dengan Kepatuhan Penggunaan APD pada Karyawan PT. TWBPK - Susan Rendra Utama R; Gusti Widyaningsih (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2026)
Occupational accidents and work-related diseases in Indonesia continue to show significant numbers, with negligence in implementing Occupational Health and Safety (OHS) procedures, including the use of Personal Protective Equipment (PPE), being one of the main causes. Data from the 2022 National OHS Profile of Indonesia indicates an increase in workplace accidents, resulting in significant losses for both workers and companies. Therefore, this study aims to analyze the factors associated with compliance with the use of PPE among employees at PT. TWBPK, a company engaged in the processing of cassava into tapioca flour. The study used a quantitative approach with a cross-sectional research design. A total of 98 respondents who met the study criteria were randomly selected from the employee population. The variables studied included age, education level, and OHS training as independent variables, and PPE compliance as the dependent variable. Data were collected through a questionnaire and analyzed using univariate and bivariate analysis with Chi-Square tests. The results showed that age, education level, and OHS training were significantly associated with compliance with PPE usage. Older workers (≥35 years) were more compliant in using PPE, workers with higher education were more likely to adhere to PPE usage, and workers who had received OHS training showed higher compliance with PPE usage. The results of this study are expected to serve as a basis for PT. TWBPK to design more effective policies in improving workplace safety and preventing accidents due to negligence in using PPE.